Presenting the model of recruitment and selection of human resources of the public sector with the approach of the entrepreneurial government - Atieh sarayani; Vahid pourshahabi; Nourmohammad yaghobi; Amin reza kamaliyan (مدیریت و چشم انداز آموزش)
Abstract The purpose of this research is the model of recruitment and selection of human resources of the public sector with the approach of the entrepreneurial government. This research is applicable in terms of its purpose, qualitative in terms of the data collection method, and a meta-composite approach in terms of the research implementation method. The statistical population of the research includes all elites and university professors and relevant experts in the field of human resources and entrepreneurial government in Sistan and Baluchistan province, whose number in 2020 is about 200 people, who were selected non-randomly in a purposeful way. Meta-composition method was used for data analysis. Extraction of components and indicators was obtained from background investigation and theoretical foundations, and then coding was used for analysis. According to the data analysis, 545 final codes were extracted through open coding and then, using axial coding were categorized in the form of 121 concepts and 16 categories; contextual (environmental) factors, structural (organizational) factors, behavioral (content) factors, Recruiting human resources, selecting human resources, identifying entrepreneurial opportunities in the public sector, exploiting entrepreneurial opportunities in the public sector, executive and managerial obstacles, political and legal obstacles, economic obstacles, cultural and social obstacles, combined selection with domination of internal resources in experience-based jobs, combined selection with the domination of external resources in knowledge-based jobs, individual consequences, organizational consequences, social consequences, and finally, in the stage of selective coding, the process and multidimensional model has been presented for the first time at the level of government organizations of Sistan and Baluchistan province. Extended abstract Introduction Human resource management is often considered as an effective approach in managing people, and its function has evolved from being only responsible for keeping records to being a strategic partner. One of the new roles of human resource management is the development of innovation and entrepreneurship. In this regard, many governments around the world believe that entrepreneurship is the key to economic development; therefore, many governments have started to offer entrepreneurship development programs. Since the theories of "entrepreneurial government" or "government entrepreneurship" were proposed by Osborn & Geabler (1992), government organizations have been keenly seeking to make changes in their management patterns, so that they can benefit from hidden advantages within these theories, which are partly derived from the management of the private sector. One of the necessary changes in this field is related to the field of human resources management as one of the internal components of government organizations (Narula & Chaudhary, 2018). Today, organizational entrepreneurship improves productivity at various individual and organizational levels, which requires a suitable foundation in the organization, therefore, flourishing in today's evolving world belongs to the societies and organizations that establish a meaningful relationship between their management capabilities and entrepreneurship of their human resources and organization; in the other word, any society or organization can move forward in the direction of development provided that by creating suitable platforms, manage the valuable human resource management system of other resources of society and organization so as to create value and acquire growth and development. The results of the studies of Hasanzade et al, (2019, 2020) and Hasani Sadrabadi (2017) in Iran's government organizations show that the establishment and use of entrepreneurial initiatives in Iran's government organizations have not been successful, and the improvement of management characteristics and entrepreneurship in these organizations requires structural and sustainable changes in public administration. Unfortunately, the current situation cannot be improved, unless efforts are made to develop human resource management development policies that can cause real and entrepreneurial changes in the state and behavior of managers and employees. Despite the mentioned issues, it seems that the human resource management system can help to promote organizational entrepreneurship in government organizations (Ahmadi et al, 2012). Therefore, according to the issues raised, the current research intends to answer the question; what is the model of recruitment and selection of human resources in the public sector with the entrepreneurial government approach? Theoretical Framework Recruitment and selection of human resources Recruitment and selection includes actions and activities carried out by an organization in order to identify and attract people in the organization who have the ability to help the organization to achieve its strategic goals. Specifically, such activities should create a pool of desirable candidates; increase their interest and attraction to the organization as an employer, and increase the likelihood that they will accept a job offer (Teimouri et al, 2018). Entrepreneurial government According to Morris & Jonse (1999), entrepreneurship in the public or government sector is the process of creating value for citizens by bringing together a unique combination of public or private resources in order to take advantage of social opportunities. In the other word; Government entrepreneurship is an organizational process that includes the improvement and development of current and new services and programs, technological innovation (techniques, procedures and laws and new administrative and selection processes) and organizational innovation (new management processes and new structuring methods) in the public sector, through the application of a new model of resource allocation to create value for citizens (Hasanzade et al, 2019). Gheiravani et al, (2023) investigated the purpose of providing a smart governance model focusing on the development and training of human resources in the public sector. The results showed that all the components of smart governance in the public sector were identified and their significance was confirmed in the research, and by examining themes, concepts and quantitative and qualitative research, the smart governance model was explained with a focus on the development and training of human resources in the public sector. Fazlali & Moazzami (2022) investigated the effect of organizational leadership style on human resource management while emphasizing the mediating role of competitive work environment. The results of the research show that organizational leadership style has no significant effect on human resource management and has been rejected; however, the significant effect of organizational leadership style on the competitive work environment, the competitive work environment on human resource management, and the organizational leadership style on human resource management with the mediating role of the competitive work environment has been confirmed. Research methodology This research is applicable in terms of its purpose, qualitative in terms of the method of data collection, and a meta-composite approach in terms of the research implementation method. The statistical population of the research includes all elites and university professors and relevant experts in the field of human resources and entrepreneurial government in Sistan and Baluchistan province, whose number in 2020 is about 200 people, who were selected non-randomly in a purposeful way. Research findings For data analysis, meta-combination method was used. Extraction of components and indicators was obtained from background investigation and theoretical foundations, and then coding was used for analysis. According to the data analysis, 545 final codes were extracted through open coding and then, using axial coding, were categorized in the form of 121 concepts and 16 categories; contextual (environmental) factors, structural (organizational) factors, behavioral (content) factors, Recruiting human resources, selecting human resources, identifying entrepreneurial opportunities in the public sector, exploiting entrepreneurial opportunities in the public sector, executive and managerial obstacles, political and legal obstacles, economic obstacles, cultural and social obstacles, combined selection with domination of internal resources in experience-based jobs, combined selection with the domination of external resources in knowledge-based jobs, individual consequences, organizational consequences, social consequences, and finally, in the stage of selective coding, the process and multidimensional model has been presented for the first time at the level of government organizations of Sistan and Baluchistan province. Conclusion The current research was conducted with the aim of recruiting and selecting human resources of the public sector with the entrepreneurial government approach. According to the obtained results, the present research is aligned with the results of Gheiravani et al, (2023), Fazlali & Moazzami (2022), Munaty et al, (2022), Fitri et al, (2021), Orakwue & Iguisi (2020), Moustaghfir (2020), Barani et al, (2022), Hasanzade et al, (2020), Noroozian et al, (2020), Tabatabai Mazdabadi et al, (2020), Sajadi Parsa et al, (2020), Narula & Chaudhary (2018). Narula & Chaudhary (2018) showed that entrepreneurship is a commitment in which a certain person goes through favorable opportunities by successfully exploiting available resources. Entrepreneurs cannot run a business alone. An entrepreneur must hire, assign people to various tasks, influence employees and retain and prepare them for the growth and development of the company. Since there are many things that need to be done from the establishment to the growth of a company, the entrepreneurial process facilitates the needs of human resource management practices. This research highlighted the relationship between human resource management methods and context and entrepreneurship. According to the obtained results, the following suggestions are provided: All recruitment processes in government organizations should have scientific and legal processes, so that in addition to reducing administrative corruption, employment justice is also established in the government departments of the province. Double emphasis on the necessity of meritocracy in the appointment of public sector managers of Sistan and Baluchistan province and paying attention to their entrepreneurial personality traits at the time of selection Revision of the job description in the public sector jobs of Sistan and Baluchistan province, emphasizing the entrepreneurial aspects of the jobs.